A cross-cultural perspective on God's personhood - Dattagupta, Akṣaẏakumāra (Religious studies, 2025)
Debates about God's personhood, or lack thereof, are central to philosophy of religion. This article aims to advance these debates by presenting the ‘greatness of personhood argument’ for God's personhood and a dilemma for those who deny God's personhood. I also consider various objections to this argument and this dilemma and argue that they fail. Notably, my reasoning in defence of personal theism is cross-cultural insofar as personal theists across various religious traditions can use it. Thus, this article defends personal theism in a manner that can bring Western and non-Western theists into closer dialogue regarding the topic of God's personhood.